Whole Genome Re-sequencing and Bulk Segregant Analysis Reveals Chromosomal Location for Papaya Ringspot Virus W Resistance in Squash - Shrestha, Swati; Fu, Yuqing; Michael, Vincent Njung’e; Meru, Geoffrey (Frontiers in Plant Science, 2022)
Squash (Cucurbita moschata) is among the most important cucurbit crops grown worldwide. Plant pathogen, Papaya ringspot virus W (PRSV-W) causes significant yield loss in commercial squash production globally. Development of virus-resistant cultivars can complement integrated disease management and mitigate losses due to viral infections. However, the genetic loci and molecular markers linked to PRSV-W resistance that could facilitate marker assisted selection for accelerated cultivar development are unknown. In the current study, quantitative trait loci (QTL), molecular markers and candidate genes associated with PRSV-W resistance in squash were identified in an F2 population (n= 118) derived from a cross between Nigerian Local accession (resistant) and Butterbush cultivar (susceptible). Whole genome re-sequencing based bulked segregant analysis (QTLseq method) and non-parametric interval mapping was used to identify a major QTL associated with PRSV-W resistance on Chromosome 9 (QtlPRSV-C09) (p-value < 0.05) of C. moschata. QtlPRSV-C09 extended from 785,532 bp to 5,093,314 bp and harbored 12,245 SNPs among which 94 were high-effect variants. To validate QtlPRSV-C09, thirteen SNP markers were assayed as Kompetitive allele specific PCR (KASP) markers in the F2 population and tested for association with PRSV-W resistance. Among these, two KASP markers (Ch09_2080834 and Ch09_5023865-1) showed significant association with PRSV-W resistance (p-value < 0.05; LOD > 2.15). The two SNPs were located within exons of putative disease resistance genes encoding the Clathrin assembly family and actin cytoskeleton-regulatory complex proteins, which are implicated in disease resistance across plant species. The findings of this study will facilitate marker-assisted selection for PRSV-W resistance in squash and allow further understanding of the functional mechanisms underlying potyvirus resistance in Cucurbita species.